2016
DOI: 10.1083/jcb.201601023
|View full text |Cite
|
Sign up to set email alerts
|

Multiciliated cell basal bodies align in stereotypical patterns coordinated by the apical cytoskeleton

Abstract: Herawati et al. developed a long-term and high-resolution live imaging system for cultured mouse tracheal multiciliated cells. Using both experimental and theoretical studies, they reveal the developmental principle of ciliary basal body alignment directed by apical cytoskeletons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
143
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(154 citation statements)
references
References 65 publications
10
143
1
Order By: Relevance
“…These two observations suggest that the microtubule-network formation is associated with the pre-existing intermediate filaments. In addition, the existence of cytoskeletal linker proteins such as plectin in the apical cytoskeletal networks supports the idea that mutual regulation between intermediate filaments, actin filaments, and microtubules plays a critical role in their function and organization, along with the specific functions of each filament network24. A deeper understanding of the mechanisms by which intermediate filaments control other filaments and/or the differentiation of tracheal MCCs should provide novel insight into the functions of these filaments.…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…These two observations suggest that the microtubule-network formation is associated with the pre-existing intermediate filaments. In addition, the existence of cytoskeletal linker proteins such as plectin in the apical cytoskeletal networks supports the idea that mutual regulation between intermediate filaments, actin filaments, and microtubules plays a critical role in their function and organization, along with the specific functions of each filament network24. A deeper understanding of the mechanisms by which intermediate filaments control other filaments and/or the differentiation of tracheal MCCs should provide novel insight into the functions of these filaments.…”
Section: Resultsmentioning
confidence: 66%
“…In the adult mouse tracheal MCCs, however, we observed three intense signals: two layers in the apical region and a microvillus-derived signal on the surface (Figs 2A,B and S2). We previously reported that the effects of depolymerizing reagents in cultured mouse MCCs are different from those in Xenopus24. Several differences between the Xenopus epidermis and mouse tracheal MCCs, such as the ciliary density and the presence of microvilli, could explain these variations.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Finally, the prospect of a correlation between Albatross function and multiple‐ciliogenesis and centriole multiplication may be attractive (Herawati et al, ; Spassky & Meunier, ; Tang, ) because Albatross localizes to the ciliary base in the mouse bronchus and even at multiplicated centrioles before ciliogenesis in normal human bronchial epithelial cells undergoing differentiation at the air–liquid interface (ALI, Supporting Information Figure S1d,e; Suprynowicz et al, ; You, Richer, Huang, & Brody, ). Genome‐editing methods that can analyze single‐nucleotide mutations (Kwart, Paquet, Teo, & Tessier‐Lavigne, ; Ochiai et al, ) will be necessary to further understand the centrosomal function of Albatross.…”
Section: Discussionmentioning
confidence: 99%
“…These are only two of the examples where our findings are likely to hold true. There are multiple other instances, whereupon maturing and differentiating epithelial cells develop an apical microtubule meshwork, including cells of mammalian airways, and even cells in culture [16,56,57]. Furthermore, the same rules are likely to apply to squamous cells, where despite having specialized apical microtubules, the cells' depth is so small, that microtubules are constrained within a thin plane similar to that in our experimental model [58,59].…”
Section: Our System Is a Particular But Generalizable Scenariomentioning
confidence: 55%